Recent progress on the role of non-coding RNA in postoperative cognitive dysfunction - Yang, Yu-Shen; He, Shi-Ling; Chen, Wei-Can; Wang, Cong-Mei; Huang, Qiao-Mei; Shi, Yan-Chuan; Lin, Shu; He, He-fan (Frontiers in Cellular Neuroscience, 2022)
Postoperative cognitive dysfunction (POCD), especially in elderly patients, is a serious complication characterized by impairment of cognitive and sensory modalities after surgery. The pathogenesis of POCD mainly includes neuroinflammation, neuronal apoptosis, oxidative stress, accumulation of Aβ, and tau hyperphosphorylation; however, the exact mechanism remains unclear. Non-coding RNA (ncRNA) may play an important role in POCD. Some evidence suggests that microRNA, long ncRNA, and circular RNA can regulate POCD-related processes, making them promising biomarkers in POCD diagnosis, treatment, and prognosis. This article reviews the crosstalk between ncRNAs and POCD, and systematically discusses the role of ncRNAs in the pathogenesis and diagnosis of POCD. Additionally, we explored the possible mechanisms of ncRNA-associated POCD, providing new knowledge for developing ncRNA-based treatments for POCD.